2003
DOI: 10.1038/sj.bjc.6600751
|View full text |Cite
|
Sign up to set email alerts
|

A33scFv–cytosine deaminase: a recombinant protein construct for antibody-directed enzyme-prodrug therapy

Abstract: A recombinant fusion protein of colon carcinoma binding A33 single chain antibody with cytosine deaminase displayed specific antigen binding and enzyme activity in surface plasmon resonance and is catalytic activity assay. In vitro, it selectively increased the toxicity of 5-FC to A33 antigen-positive cells by 300-fold, demonstrating the potency of this ADEPT strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Although genetically fused antibody/enzyme conjugates can be produced, we, and others, have observed that the production levels of these conjugates are frequently very low [7][8][9]. In fact, our initial attempt to produce an antibody-FCU1 fusion protein in myeloma cells was unsuccessful because of low production levels (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetically fused antibody/enzyme conjugates can be produced, we, and others, have observed that the production levels of these conjugates are frequently very low [7][8][9]. In fact, our initial attempt to produce an antibody-FCU1 fusion protein in myeloma cells was unsuccessful because of low production levels (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative approach, recombinant DNA technology could be used to prepare homogeneous antibody-enzyme fusion proteins. However, for reasons we have yet to understand, production levels of such fusion proteins are often very low, limiting their use in clinical (or sometimes even animal) studies [7][8][9]. In addition, this strategy requires that a different fusion protein be produced for every antibody/enzyme combination, which is cumbersome, and there may be a decrease in activity of one or both covalently linked partners.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…115 This antibody fragment is known to target the A33 antigen, which is expressed by the majority of primary and metastatic colorectal tumors. 116 The A33scFv-targeted NPs were selectively internalized by colorectal SW1222 xenograft tumors over non-A33-expressing cells. Subsequently, these tumors underwent laser-assisted photothermal treatment (808 nm, 5 W − 1 cm − 2 ) which adversely affected more than 65% of A33-expressing SW1222 cells by damaging the ECM and cytoplasmic acidophilia.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…CD enzyme was modified to obtain targeting specificity by conjugation with antibodies that were able to direct enzyme to the tumor cell surfaces (Senter et al, 1991;Wallace et al, 1994;Deckert et al, 2003). These modifications have been shown to increase antitumor activities in combination with prodrug 5-FC partly due to increase in intratumoral drug concentrations.…”
Section: Transduction Of Yeast Cytosine Deam Inase M Ediated By Hiv-1mentioning
confidence: 99%